2002
DOI: 10.1038/sj.onc.1205701
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of HTLV-1 Tax with HDAC1 negatively regulates the viral gene expression

Abstract: Histone acetyltransferases (HATs) and histone deacetylases (HDACs) are known to interact with several transcription factors and regulate their transcriptional activities. The human T-cell leukemia virus type 1 (HTLV-1) Tax oncoprotein activates transcription from its long terminal repeat (LTR) through interaction with cellular factors such as CREB and a transcriptional coactivator CBP/p300. However, little is known about the interaction between Tax and transcriptional repressors. Here, we demonstrate the physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 30 publications
4
63
0
Order By: Relevance
“…32 Recently, it has been shown that human T-cell leukemia virus type 1 (HTLV-1) Tax protein, which activates transcription from its long terminal repeat by interacting with p300/CBP and CREB, can negatively regulate the gene expression by binding with HDAC1. 33 These cases have a similarity with the relationship of SYT and mSin3A shown in the present study. The mSin3A/HDAC complex might negatively regulate the transcriptional activation mediated by SYT which is associated with transcriptional coactivators such as p300.…”
Section: Discussionsupporting
confidence: 62%
“…32 Recently, it has been shown that human T-cell leukemia virus type 1 (HTLV-1) Tax protein, which activates transcription from its long terminal repeat by interacting with p300/CBP and CREB, can negatively regulate the gene expression by binding with HDAC1. 33 These cases have a similarity with the relationship of SYT and mSin3A shown in the present study. The mSin3A/HDAC complex might negatively regulate the transcriptional activation mediated by SYT which is associated with transcriptional coactivators such as p300.…”
Section: Discussionsupporting
confidence: 62%
“…Efficient transcription of the HTLV-I promoter requires the formation of a transactivation complex containing Tax HTLV-I , CREB, and CBP/p300 (55). (72). Functionally, these two latter reports have shown the downregulation by HDACs of basal and Tax HTLV-I -activated HTLV-I transcription.…”
Section: Discussionmentioning
confidence: 96%
“…This mechanism is indeed rational given the opposing activities of deacetylase and acetylase, that is, that they not only counter-regulate each other catalytically but also non-catalytically (interaction). Although a recent study suggested competition between CREBbinding protein and HDAC1 for binding to a transcription factor using the lysate of cells overexpressing HDAC1 (30), this is the first description of direct competition for binding on a specific interaction region by deacetylase and acetylase.…”
Section: Insight Into Mechanism Of Negative Regulatory Effect Onmentioning
confidence: 99%
“…1F). This amino-terminal region also includes the binding site for Tax (30) and thus may be a common protein-protein interaction surface. Collectively, KLF5-DBD binds to the amino-terminal region of HDAC1.…”
Section: Klf5 and Hdac1 Can Interact In The Cell And Directlymentioning
confidence: 99%